(423) a note on life of capital and economic growth ملاحظة حول حياة رأس المال والنمو الاقتصادي - qayum, A. (the institute of national planning, 2018)
This study examines the relationship between the economic life of capital and economic growth within the framework of aggregate growth models that permit continuous substitution among factors of production. The paper aims to analyze how the productive life of capital influences methods of combining production factors and estimating their marginal productivity, while emphasizing the theoretical and practical implications of these relationships for economic growth analysis. The study begins by discussing several procedures employed in growth models to explain interactions between labor and capital. It reviews an approach associated with the work of Tinbergen, Solow, and other economists that assumes substitution possibilities among the total quantities of production factors available within the economy. Under this approach, total labor and total capital are combined through an aggregate production function used to explain growth behavior and determine factor productivity. The paper also examines an alternative approach based on the assumption that substitution possibilities exist before investment decisions are implemented but not afterward. According to this method, new investment flows are combined with available labor supplies, creating a different interpretation of the relationship between investment processes and capital accumulation dynamics. The study focuses particularly on the effect of capital life on economic growth outcomes. It argues that assuming capital assets remain productive for multiple periods generates different analytical results compared with models that assume complete capital consumption within a single period. Variations in the productive life of capital influence the rate of capital accumulation, levels of output, and the marginal productivity of production factors, ultimately affecting long-term economic growth paths. The academic significance of the study lies in its contribution to growth theory through the incorporation of capital life considerations into analytical models. Such an approach improves the explanatory power of economic models and enhances their relevance for understanding real economic conditions and supporting development policy formulation.